2018
DOI: 10.1016/j.watres.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation ability of three phylogenetically distant anammox bacterial species

Abstract: Anaerobic ammonium-oxidizing (anammox) bacteria are well known for their aggregation ability. However, very little is known about cell surface physicochemical properties of anammox bacteria and thus their aggregation abilities have not been quantitatively evaluated yet. Here, we investigated the aggregation abilities of three different anammox bacterial species: "Candidatus Brocadia sinica", "Ca. Jettenia caeni" and "Ca. Brocadia sapporoensis". Planktonic free-living enrichment cultures of these three anammox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(29 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…Ali et al . (2018) demonstrate that aggregation ability of Candidatus Brocadia sinica was due to its hydrophobic surface. Hou et al .…”
Section: Discussionmentioning
confidence: 99%
“…Ali et al . (2018) demonstrate that aggregation ability of Candidatus Brocadia sinica was due to its hydrophobic surface. Hou et al .…”
Section: Discussionmentioning
confidence: 99%
“…Ali et al. (2018) reported that Candidatus Brocadia sinica cells have the most hydrophobic surface and fewer hydrophilic functional groups in extracellular polymeric substances, which results in a better aggregate capability than that of Candidatus Jettenia caeni and Candidatus Brocadia sapporoensis. These results implied that the existing form of anammox sludge in the bioreactor might be conspicuously related to the bacterial species of seeding sludge.…”
Section: Configurations For Mainstream Application Of Anammoxmentioning
confidence: 99%
“…The available literature [ 32 , 33 , 34 , 36 ] highlights the practicality of NMR in drug design studies. For these reasons, NMR spectroscopy is highly sought after in drug development [ 37 , 38 , 39 , 40 , 41 ], for both molecule identification [ 11 , 13 , 14 , 18 , 42 , 43 , 44 , 45 , 46 ] and structural elucidation [ 15 , 16 , 17 , 45 , 47 , 48 , 49 , 50 , 51 ]. NMR has been successfully applied in stereochemistry [ 52 , 53 , 54 , 55 , 56 ] and isomer determination [ 57 , 58 , 59 , 60 , 61 ], in drug-protein interactions studies [ 62 , 63 , 64 ], and in the evaluation of drug toxicity [ 65 , 66 , 67 , 68 ].…”
Section: Introductionmentioning
confidence: 99%